A Survey on hierarchical cluster-based energy efficient routing protocol for wireless sensor networks - Khan, Humera (International Journal of Engineering and Technology, 2018)
Wireless Sensor Network is a widely growing field and it comprises of tiny sensor nodes. These sensor nodes are distributed in the environment spatially. They are capable of sensing the environment, gathering the information and processing it. Each sensor node collaborate with other sensor nodes for processing the information. Sensor nodes have very limited resources available for their operation. For the purpose of consuming resources in an efficient way several routing algorithms are employed. Here the focus is mainly on hierarchical cluster based routing techniques. In this paper we provide an introduction for wireless sensor network, the requirement for reduction in energy consumption of sensor nodes and some of the already existing energy efficient routing protocols of wireless sensor network.